Dual-responsive supramolecular photodynamic nanomedicine with activatable immunomodulation for enhanced antitumor therapy - He, Siqin; Wang, Lulu; Wu, Dongxu; Tong, Fan; Zhao, Huan; Li, Hanmei; Gong, Tao; Gao, Huile; Zhou, Yang (Acta pharmaceutica Sinica. B, 2024)
A major challenge facing photodynamic therapy (PDT) is that the activity of the immune-induced infiltrating CD8+ T cells is subject to the regulatory T lymphocytes (Tregs), leaving the tumor at risk of recurrence and metastasis after the initial ablation. To augment the antitumor response and reprogram the immunosuppressive tumor microenvironment (TME), a supramolecular photodynamic nanoparticle (DACss) is constructed by the host-guest interaction between demethylcantharidin-conjugated β-cyclodextrin (DMC-CD) and amantadine-terminated disulfide-conjugated FFVLGGGC peptide with chlorin e6 decoration (Ad-ss-pep-Ce6) to achieve intelligent delivery of photosensitizer and immunomodulator for breast cancer treatment. The acid-labile β-carboxamide bond of DMC-CD is hydrolyzed in response to the acidic TME, resulting in the localized release of DMC and subsequent inhibition of Tregs. The guest molecule Ad-ss-pep-Ce6 can be cleaved by a high level of intracellular GSH, reducing photosensitizer toxicity and increasing photosensitizer retention in the tumor. With a significant increase in the CTL/Treg ratio, the combination of Ce6-based PDT and DMC-mediated immunomodulation adequately achieved spatiotemporal regulation and remodeling of the TME, as well as improved primary tumor and in situ lung metastasis suppression with the aid of PD-1 antibody. Dual-responsive cyclodextrin-based supramolecular self-assembly system co-delivers photosensitizer and immunomodulator to induce tumor cell apoptosis and reverse the immunosuppressive microenvironment with PD-1 antibody for effective treatment of metastatic breast cancer. [Display omitted]